2012
DOI: 10.1021/ml3000935
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Functionalization of Cyclic Sulfonimidamides: A Novel Chiral Heterocyclic Carboxylic Acid Bioisostere

Abstract: An efficient synthesis of aryl substituted cyclic sulfonimidamides designed as chiral nonplanar heterocyclic carboxylic acid bioisosteres is described. The cyclic sulfonimidamide ring system could be prepared in two steps from a trifluoroacetyl protected sulfinamide and methyl ester protected amino acids. By varying the amino acid, a range of different C-3 substituted sulfonimidamides could be prepared. The compounds could be further derivatized in the aryl ring using standard cross-coupling reactions to yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 19 publications
0
41
0
Order By: Relevance
“…[1] Typical examples include the exchange of hydrogen with deuterium [2] or fluorine, [3] and new types of bioisosteres for common functional groups (such as CO 2 H) continue to be developed. [4] While chloro and methyl substituents at sp 2 -hybridized carbon atoms are routinely interchanged in the process of optimizing the properties of alead structure, [5] the analogous Cl$Me interchange at stereogenic sp 3 -hybridized carbons is less explored in biologically active small molecules. [6] Seeking to fill this gap,h erein we report the synthesis and biological evaluation of two analogues of anaturally occurring inhibitor of complex II in the mitochondrial respiratory chain, atpenin A5 (1;Scheme 1).…”
mentioning
confidence: 99%
“…[1] Typical examples include the exchange of hydrogen with deuterium [2] or fluorine, [3] and new types of bioisosteres for common functional groups (such as CO 2 H) continue to be developed. [4] While chloro and methyl substituents at sp 2 -hybridized carbon atoms are routinely interchanged in the process of optimizing the properties of alead structure, [5] the analogous Cl$Me interchange at stereogenic sp 3 -hybridized carbons is less explored in biologically active small molecules. [6] Seeking to fill this gap,h erein we report the synthesis and biological evaluation of two analogues of anaturally occurring inhibitor of complex II in the mitochondrial respiratory chain, atpenin A5 (1;Scheme 1).…”
mentioning
confidence: 99%
“…Sulfonimidamide is an isostere of sulphonamide, which is formed by replacing one of the O-atoms by nitrogen of sulfonamide. The title compound can be considered as a potential pecursor for the preparation of sulfonimidamids [9][10][11][12]. However crystal structures of sulfinylcarbamate derivatives are rare.…”
Section: Discussionmentioning
confidence: 99%
“…For the free acyl sulfonimidamide 20, we found that tautomer A is more stable by 2.4 kcal mol À1 than tautomer B, which is in agreement with related calculations for the cyclic analogue 7. [25] Clearly, the calculations suggest that the imine prefers to be conjugated with an acyl carbonyl, but also that protonation on the nitrogen atoms is significantly more preferred over protonation of the oxygen atoms (tautomers C and D).…”
mentioning
confidence: 93%
“…N-acyl- (20)(21)(22)(23)(24)(25), N-acyl-N'-carbamoyl- (16)(17), and N,N'-diacyl-(18) sulfonimidamides possess interesting structural features, as they may undergo tautomerization, placing the acidic proton on either of the two nitrogen atoms, and possibly on the two oxygen atoms, as illustrated in Figure 2. We undertook some initial density functional theory (DFT) calculations on this tautomeric equilibrium (B3LYP/6-311 + G** with a PBF solvent model for water).…”
mentioning
confidence: 99%